Effects of Al:Si and (Al+Na):Si ratios on the static corrosion of sodium‐boroaluminosilicate glasses. (17th June 2021) - Reiser, Joelle T.; Parruzot, Benjamin; Gin, Stéphane; Bonnett, Jeffrey F.; Smoljan, Courtney S.; Seymour, Lorraine M.; Ryan, Joseph V.; Vienna, John D.
Abstract: Understanding alteration mechanisms of borosilicate glasses in aqueous media is essential to nuclear waste performance assessments to ensure radioisotopes are contained for extended durations. Aluminum is typically added to glass compositions to reduce the extent of alteration. However, previous work on 7‐day durability tests has suggested that Al has a nonlinear relationship with extent of alteration. The effects of Al:Si and (Al+Na):Si substitutions on glass durability were evaluated using series of glasses based on the International Simple Glass corroded in static conditions up to 13 months in deionized water at 90°C. The alteration behavior was determined by measurement of element release in solution. The ⁓7‐day alteration trends across the series were consistent with predicted trends. The 13‐month results indicated overall alteration decreased as Al:Si ratios increased and was unaffected by changes in (Al+Na):Si except for the glass with the highest (Al+Na):Si ratio (ISG‐A23N), which completely altered within 14 days. Frequent sampling and in situ Raman measurements of solutions revealed ISG‐A23N experienced several distinguishable alteration rate regimes within 7 days, forming a ⁓100 µm alteration layer and a NaSiAlO4 zeolite.